Baseline assessment of water quality and ecological indicators in Penaeus vannamei farm wastewater along the Southeast coast of India. (November 2020) - Dinesh Kumar, S.; Santhanam, P.; Krishnaveni, N.; Raju, P.; Begum, A.; Ahmed, S.U.; Perumal, P.; Pragnya, M.; Dhanalakshmi, B.; Kim, Mi-Kyung
Abstract: The present study aimed to investigate the water quality characteristics and the ecological indicators of wastewater of white legged shrimp Penaeus vannamei ponds along the Southeast coast of India. The wastewater samples were collected from 15 shrimp farms covering 11 districts located along the coastal line of Tamil Nadu and Puducherry, India. By adopting standard methods, the collected samples were subjected to analyses of physico-chemical and biological characteristics, especially the microbial load and metal and plankton composition. The nitrate-nitrogen, ammonia-nitrogen, THB, TCB, and Cu concentrations of the samples were found to exceed the permissible limit as recommended by WHO, USEPA, CPCB, and CAA. Principal component analysis and canonical correspondence analysis have suggested that the phosphate, nitrate, silicate, ammonia, and total phosphorus are the important chemical factors. The generated data would be of interest to farmers for their shrimp crop management vis-à-vis culture pond wastewater treatment. Highlights: Penaeus vannamei cultured wastewaters significantly contribute to nutrients pollution. This study covers 1076 km coastal area consisting 15 farms in 11 districts from tow states. Higher level of NO3, NH3, THB, TCB, Cu detected in wastewater than the permissible limit Plankton diversity was triggered by higher loading of nutrients. PCA and CCA suggest that total nitrogen plays vital role in wastewater.